PERAN PROGRAM BUMN GO GLOBAL TERHADAP PENGUATAN DIPLOMASI EKONOMI INDONESIA - Mayra Zahabiya Zahra; Windy Dermawan; Fuad Azmi (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study examines the role of the BUMN Go Global program as an instrument of Indonesia’s economic diplomacy amid increasing global economic fragmentation. Using a qualitative approach based on document analysis of official policies and institutional reports, the study analyzes how Indonesian state-owned enterprises (BUMNs) expand internationally through overseas operations, strategic partnerships, and outbound investments supported by diplomatic institutions. The findings indicate that the program strengthens Indonesia’s economic diplomacy by enhancing national economic representation, reinforcing bilateral economic relations, and supporting nation branding through BUMN-led international projects. The study further shows that BUMNs function as semi-state actors operating at the intersection of commercial objectives and foreign policy strategy. However, structural challenges persist, including inter-agency coordination gaps, internal capacity disparities, and regulatory and political risks in host countries. Overall, the study highlights the growing role of state-owned enterprises in shaping contemporary economic diplomacy beyond traditional diplomacy and contributes to the literature by positioning BUMNs as semi-state diplomatic actors in global governance.